The literary theory handbook - Castle, Gregory (Blackwell Literature Handbooks, 2013)
The Literary Theory Handbook introduces students to the history and scope of literary theory, showing them how to perform literary analysis, and providing a greater understanding of the historical contexts for different theories. A new edition of this highly successful text, which includes updated and refined chapters, and new sections on contemporary theoriesFar reaching in its inclusion of a detailed history of theory and in-depth discussions of major theories and movementsFour distinct perspectives on theory historical, thematic, biographical, practical are carefully intertwined, so that key concepts, terms and ideas are developed in different contexts and cross-referenced, in the text and in the index.Includes alphabetically-arranged biographies designed for quick reference, and sample readings to illustrate the practical application of theory